ANALISIS MASALAH KESEHATAN KABUPATEN BANTUL - Maftuhah Nurbetl; Syamsumin Kurnia Dewi (Faculty of Medicine, Universitas Islam Indonesia, 2009)
Three years after great earthquake on May 2006, Bantul has succeeded to be recovered in many sectors, including health. However, Bantul still face many health problems that should be overcome in their limited resources. Therefore,this research identify, analyze, and set the priorities of health problems in order to give recommendations-for eficient and effective health policies and program planning in Bantul. This analysis is a descriptive observational research whichanalyzes secondary data from the Health Department of Bantul District. Health problem priority was set using Hanlon method. In a series, the top ten priority health problem are Maternal mortality, HIV/AIDS, Infant mortality, Tuberculosis,Diabetes Mellitus, Dengue Haemorhagic Fever, Hypertension, Malnutrition, mortality of children under five, and Diarrhea. Thereby, Bantul district still has double burden. In one side, infectious diseases are still in a high rate. On theother hand, the degenerative diseases also proceed to increase and reach a great number of sufferer.